Serum leptin levels in male marathon athletes before and after the marathon run - Leal-Cerro, A.; Garcia-Luna, P. P.; Astorga, R.; Parejo, J.; Peino, R.; Dieguez, C.; Casanueva, F. F. (1998)
Leptin is a hormone produced by the adipocytes to regulate food intake and energy expenditure at the hypothalamic level. It is commonly accepted that the main determinants of leptin secretion are the net amount of body fat and the mean size of adipocytes. On the contrary, important vectors of energy flux in the organism, such as food intake and energy expended on exercise, are not thought to be regulators of that secretion. To understand whether leptin is regulated by an acute energy expenditure such as strenuous exercise, 29 male athletes who had trained for marathon running were studied before and after a marathon run and compared with 22 nonobese, age-, sex-, and body mass index (BMI)-matched sedentary controls. Controls and marathon athletes showed no differences in BMI or fat-free mass. Marathon runners showed a strong reduction in total fat mass (6.2 +/- 0.4 kg; 9.1 +/- 0.5% of body fat) compared with controls (12.3 +/- 0.5 kg; 16.1 +/- 0.5% of body fat; P < 0.05). This difference in body composition was paralleled by a mean serum leptin level that in marathonians (2.9 +/- 0.2 micrograms/L) was significantly (P < 0.05) reduced compared with that in controls (5.1 +/- 0.6 micrograms/L). It is remarkable that the ratio of leptin per kg body fat, showed a very good agreement between the two groups, 0.40 +/- 0.04 microgram/L.kg for controls and 0.46 +/- 0.03 microgram/L.kg for marathonians. In the two groups, leptin was correlated with both body weight, BMI, and fat mass (P < 0.001). The marathon trajectory was the standard 42.195 km accomplished in an average time of 3 h, 17 min, 7 s, with a calculated energy expenditure of over 2800 Cal. After the marathon run, a water imbalance occurred, with a significant decrease in body weight and an increase in serum albumin. A significant (P Z 0.05) reduction in leptin values was observed after the run (2.6 +/- 0.2 micrograms/L) compared with before (2.9 +/- 0.2 micrograms/L), which was more relevant considering the relative hemoconcentration. In conclusion, 1) compared with sedentary subjects, leptin levels are reduced in male marathon runners in parallel with the relevant reduction in total body fat; 2) expressed as a ratio of leptin per kg body fat, no differences were observed between marathonians and controls; and 3) after an energy expenditure of 2800 Cal in the marathon run, a reduction in leptin levels occurred. Strong changes in energy expenditure may regulate serum leptin levels in man. J Clin Endocrinol Metab 1998 Jul;83(7):2376-9